Arbitragem tributária no cenário nacional : perspectiva constitucional e comparada - Soria, Juliana Sirotsky (2017)
The following work aims to examine the possibility of using arbitration as an alternative dispute technique within tax law disputes in Brasil. To do so it will analyze the prospects to apply said institute in light of constitutional principles and organic laws, identifying Law characteristics that, somehow, already give some kind of authorization to tax arbitration, especially trough the availability of the public interest and the tax credit, as well as the insufficient services that our national courts provide to the resolution of tax disputes. Besides, we will examine the main characteristics of arbitration as a jurisdiction and arbitrability requisites, such as capacity of the parties and availability of the rights involved. Finally, it will be demonstrated that tax arbitration in Brazilian law is a possibility, especially when compared with the existent regime in Portugal as long as the specifics and the principle of legality is observed by the authorities.